A preliminary study on the distribution and diversity of trees in Patag, Silay. - Ibarra, Merry Jo Gallera
A 0.5600-hectare area was chosen and was further divided into smaller quadrats each measuring 5 x 5 m2. The trees for each quadrat were identified. Moreover, the GBH and height of each tree were also measured and noted. From the data gathered, frequency, density, relative density, index dominance, and index of diversity were determined., There were forty species of trees identified in the North Negros Forest Reserve area. mahogany has the highest frequency and relative density among the species identified. The index of diversity is higher than the index of dominance which signified that the species of trees in the sample area were diverse and that no one species of tree dominated.